Preliminary Study on the Imbalance Between Th17 and Regulatory T Cells in Antiphospholipid Syndrome - Yan, Huanhuan; Li, Baochen; Su, Rui; Gao, Chong; Li, Xiaofeng; Wang, Caihong (Frontiers in Immunology, 2022)
Objective: Patients with antiphospholipid syndrome (APS) have immune cell abnormalities that remain poorly understood. This study compared primary APS (PAPS) and secondary APS (SAPS) patients with healthy controls with respect to peripheral blood lymphocytes, CD4+T cell subsets, and cytokine levels. The correlation between antiphospholipid antibody titres and T helper 17 (Th17) and T regulatory (Treg) cell subsets was also analyzed, together with the correlations between cytokine profiles and the clinical characteristics of APS patients. Methods: The retrospective study population consisted of 67 APS patients (12 with PAPS, 55 with SAPS) and 40 healthy controls. The Absolute numbers of peripheral blood lymphocyte subsets and CD4+ T cell subsets were detected by flow cytometry, and serum cytokine levels were detected by flow cytometry bead array. Results: Patients with SAPS had lower absolute values of T, B and CD4+T cells than the healthy control group, while only natural killer (NK) cell levels were decreased in patients with PAPS. Absolute numbers of T, B, NK, and CD4+T cells were significantly higher in the PAPS than SAPS group. The trends in CD4+T cell subsets were the same in PAPS and SAPS patients as in healthy controls, with increased Th1, decreased Th2, and decreased Treg levels, and thus an increased Th17/Treg ratio. Th2, Th17, and Treg cell counts were higher in the PAPS than SAPS group. Cytokine analysis showed that only IL-10 levels differed between the two APS groups. However, the levels of all of the studied cytokines were higher in APS patients than healthy controls, and correlated with the clinical characteristics of the patients. In the PAPS group, the titres of two autoantibodies correlated positively with the Th17/Treg ratio and negatively with the levels of D-dimer and Treg subsets. Conclusions:Our study clearly showed that APS patients have immune disturbances, the most prominent of which is an increase in the Th17/Treg ratio, due to a decrease in the number of Treg cells. These abnormalities may be involved in the occurrence and progression of APS. An additional finding was a higher level of peripheral blood lymphocytes, and thus more severe inflammation, in PAPS than SAPS patients.